2001
DOI: 10.1007/bf02463920
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic studies on new or critical fungi of non-pathogenic Onygenales 4

Abstract: Three noteworthy taxa of soil-borne onygenalean fungi are described and illustrated: Kraurogymnocarpa trochleospora, comb. nov., Kuehniella aurea, comb. nov., and Nannizziopsis albicans. In addition, Aphanoascus boninensis, which was previously described as a new species, is considered to be a synonym of Uncinocarpus orissi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…As far as we know, of the 10 most abundant phylotypes detected in the cave only Kraurogymnocarpa trochleospora has not been associated with arthropods. It was isolated from soils in Indonesia, USA and Monaco (Udagawa and Uchiyama 2001).…”
Section: Discussionmentioning
confidence: 99%
“…As far as we know, of the 10 most abundant phylotypes detected in the cave only Kraurogymnocarpa trochleospora has not been associated with arthropods. It was isolated from soils in Indonesia, USA and Monaco (Udagawa and Uchiyama 2001).…”
Section: Discussionmentioning
confidence: 99%
“…There are estimated to be as many as eight Psilocybe hallucinogenic species containing psychoactive alkaloids, such as psilocybin and psilocin. K. trochleospora (Pseudoarachniotus trochleosporu) is usually isolated from soils with high organic content and have high cellulolytic activity (Udagawa and Uchiyama 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Only one species of Gymnoascus forms bivalvate ascospores, G. ruber, whose ascospores are smooth, unlike Kraurogymnocarpa . The original authors did not perform a molecular analysis, but stated in their paper that such studies may supply more evidence on their relationships ( Udagawa & Uchiyama 2001 ). Sigler et al (2002) sequenced the SSU region of an ex-type culture of Kraurogymnocarpa trochleospora and showed that it was distinct from five species of five different genera of Gymnoascaceae , all of which are now placed in Gymnoascus ( Sole et al 2002 ).…”
Section: Discussionmentioning
confidence: 99%